Actividad enzimatica digestiva e histología intestinal en juveniles de tilapia roja (Oreochromis mossambicus x Oreochromis niloticus) alimentados con ácido ascórbico en dieta. - Jijón Montes, Joselyne Rocío (2022)
The objetive of this research was to evaluate the digestive enzyme activity and intestinal histology in juvenile red tilapia (Oreochromis mossambicus x Oreochromis niloticus) fed ascorbic acid in the diet. The research work was carried out at the "La María" Campus, belonging to the State Technical University of Quevedo. Experimental pelleted diets including ascorbic acid in doses of 0, 100, 200, 400, 800 y 1600 mg kg-1 were used; each treatment consisted of three replications (plastic aquariums), with 15 experimental units (juvenile red tilapia) /aquarium, giving a total of 270 juveniles in a completely randomized design. The culture period lasted 56 days, then the intestines were dissected, weighed and samples were taken for biochemical and histological analysis. As for the variable of the intesto-somatic index, the best result was obtained at T6 8.6±2.23% did not report statistical significance in the treatments, therefore for the digestive enzyme activity, the amylase in response at T6 was 55.74 ±1.23, in lipases it is reflected in T6 with the value of 41.05±5.04, in terms of proteases they are evident in T6 with 78.95±6.66, therefore statistical differences were found for these variables.